2014
DOI: 10.2337/dc14-0955
|View full text |Cite
|
Sign up to set email alerts
|

Contributory Factors to Unsteadiness During Walking Up and Down Stairs in Patients With Diabetic Peripheral Neuropathy

Abstract: OBJECTIVEAlthough patients with diabetic peripheral neuropathy (DPN) are more likely to fall than age-matched controls, the underlying causative factors are not yet fully understood. This study examines the effects of diabetes and neuropathy on strength generation and muscle activation patterns during walking up and down stairs, with implications for fall risk. RESEARCH DESIGN AND METHODSSixty-three participants (21 patients with DPN, 21 diabetic controls, and 21 healthy controls) were examined while walking u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Despite the speed at which strength was generated being increased significantly at both joints during stair ascent and descent, the time‐to‐peak, previously suggested to be closely related to the speed of strength generation, varied between groups (longer time‐to‐peak of the knee extensors in the diabetes intervention groups (with and without neuropathy) during stair descent, and a shorter time‐to‐peak of the knee extensors during ascent) and showed no changes in line with the increases in the speed of strength generation after the intervention that were observed previously to differentiate between participant groups (Fig a,b) . An increase in muscle strength as a result of the exercise intervention may therefore be the main causative factor for the faster strength generation observed at the ankle and knee, rather than increased speed of muscular activations.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Despite the speed at which strength was generated being increased significantly at both joints during stair ascent and descent, the time‐to‐peak, previously suggested to be closely related to the speed of strength generation, varied between groups (longer time‐to‐peak of the knee extensors in the diabetes intervention groups (with and without neuropathy) during stair descent, and a shorter time‐to‐peak of the knee extensors during ascent) and showed no changes in line with the increases in the speed of strength generation after the intervention that were observed previously to differentiate between participant groups (Fig a,b) . An increase in muscle strength as a result of the exercise intervention may therefore be the main causative factor for the faster strength generation observed at the ankle and knee, rather than increased speed of muscular activations.…”
Section: Discussionmentioning
confidence: 62%
“…The present intervention study follows on from a previously published study by this research group, in which we observed decreased knee and ankle speed of strength generation in patients with diabetes and DPN compared with control subjects during stair ascent and descent, in a larger cohort of patients . The participants from the previous study were given the option to participate in the present interventional study, but because of the time commitment associated with the intervention (1 h per week for 16 weeks, during standard working hours) fewer patients were able to commit to the 16‐week intervention programme than were originally expected.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations